Mapping Microscale Chemical Heterogeneity in Nafion Membranes with X-ray Photoelectron Spectroscopy. Issue 11 (1st January 2018) - Friedman, Alicia K.; Shi, Wenqing; Losovyj, Yaroslav; Siedle, Allen R.; Baker, Lane A.
Abstract : Nafion has found utility in a wide variety of applications, particularly as the most commonly used electrolyte membrane in fuel cell technology. Despite decades of characterization by X-ray Photoelectron Spectroscopy (XPS), a dispute exists within literature over the proper assignment of oxygen binding energies from the ether and sulfonate functional groups present in Nafion. Here, we have employed highly oriented pyrolytic graphite (HOPG) as an internal standard to calibrate all XPS spectra and are able to correlate binding energies from C1s, O1s, F1s and S2p to the Nafion structure. Further, microscale heterogeneities inherent to this formulation of Nafion membranes are revealed through two-dimensional XPS mapping of membrane cross-sections as well as surface ablation via Ar + ion sputtering. Results clearly show Nafion membranes are comprised of two chemically distinct layers: a surface layer several microns thick that is comprised of sulfonate groups and an inner layer that shields the more non-polar perfluoroether moieties.